Real-time indoor and outdoor measurements of black carbon at primary schools. (November 2015) - Reche, C.; Rivas, I.; Pandolfi, M.; Viana, M.; Bouso, L.; Àlvarez-Pedrerol, M.; Alastuey, A.; Sunyer, J.; Querol, X.
Abstract: Epidemiological and toxicological studies have demonstrated the association between Black Carbon in indoor and outdoor air and the occurrence of health risks. Data on air quality in schools is of special interest, as children are more vulnerable to health hazards. In this context, indoor and outdoor measurements of real-time Equivalent Black Carbon (EBC) were collected at 39 primary schools located in Barcelona (Spain), with classrooms naturally ventilated under warm weather conditions. A main contribution of road traffic emissions to indoor and outdoor EBC levels was evidenced through different approaches. Simultaneous measurements of EBC levels at schools under different traffic conditions revealed concentrations by 30–35% higher at schools exposed to higher vehicles intensities. Moreover, a significant correlation was obtained between average outdoor EBC levels at different districts of the city and the percentage of surface area in each district used for the road network (R 2  = 0.61). Higher indoor than outdoor levels were recorded at some instances when the indoor sampling location was relatively closer to road traffic, even under low outdoor temperatures. Indeed, the average indoor/outdoor EBC ratios for each school correlate moderately between campaigns in spite of significant differences in temperature between sampling periods. These two facts highlight the strong dependency of the EBC levels on the distance to traffic. The peaks of exposure inside the classrooms seemed to be determined by outdoor concentrations, as shown by the parallelism between indoor and outdoor mean EBC daily cycles and the similar contribution of traffic rush hours to indoor and outdoor daily mean levels. The airtightness of the classroom was suggested as the responsible for the indoor/outdoor ratios of EBC higher than 1 recorded at nights. Highlights: Indoor and outdoor Equivalent Black Carbon (EBC) measured at 39 primary schools. Indoor exposures greatly determined by outdoor concentrations. Strong dependency of indoor and outdoor EBC levels on the distance to traffic. Mean EBC at different districts related with the surface area used for road network. Indoor/outdoor ratios >1 at nights maybe linked to the airtightness of the classroom.